Cookstove startup material characterization and quantification and acute cardiopulmonary effects from controlled exposure to cookstove air pollution - Fedak, Kristen M., author; Peel, Jennifer L., advisor; Volckens, John, advisor; Clark, Maggie, committee member; Nelson, Tracy, committee member; Wilson, Ander, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.